Determinan Keputusan Pembelian: Peran Lokasi, Kualitas Produk, dan Personal Branding - Henny Purwanti; Tri Sugiarti Ramadhan (Siber Nusantara Publisher, 2026)
This study aims to analyze the influence of location, product quality, and personal branding on consumer purchasing decisions at Ghealsy in Malang City. This study uses a quantitative approach with a probability sampling technique through a simple random sampling method. The number of samples was determined using the Malhotra formula, resulting in 110 respondents. Data analysis methods used include instrument testing (validity and reliability tests), normality tests, and classical assumption tests consisting of multicollinearity and heteroscedasticity tests. Furthermore, the data were analyzed using multiple linear regression with hypothesis testing through simultaneous tests (F tests), partial tests (t tests), and coefficients of determination (R²). The results show that location, product quality, and personal branding simultaneously have a positive and significant influence on purchasing decisions. Partially, each variable, namely location, product quality, and personal branding, is also proven to have a positive and significant influence on consumer purchasing decisions.keywords: location, product quality, personal branding and purchasing decisions.